Species of Acryptolaria Norman, 1875 (Cnidaria: Hydrozoa) collected by US Antarctic and sub-Antarctic expeditions - Cantero, Álvaro L. Peña (Zootaxa, 2020)
Acryptolaria is a worldwide genus of deep-water benthic hydroids. The genus has relatively high species diversity, with 36 species described so far, yet most of them have been reported only occasionally. As a result, scientific knowledge of their ecology and distribution is scarce. Here I present the results of the study of species of Acryptolaria collected during several Antarctic and sub-Antarctic expeditions under the United States Antarctic Research Program between 1958 and 1986. Eight species were found in the collection (plus one determined to the genus level), with A. operculata having the highest occurrence. Acryptolaria flabellum is reported for the second time; the study also represents the third record for A. corniformis and A. minuta. Despite the scarcity of records, most of the species studied seem to have a wide geographical distribution, which could be related to their deep-water bathymetric distribution and the deep-water circulation of the Great Ocean Conveyor Belt.